2008
DOI: 10.1021/jp076067r
|View full text |Cite
|
Sign up to set email alerts
|

Arsenate Incorporation in Gypsum Probed by Neutron, X-ray Scattering and Density Functional Theory Modeling

Abstract: 2The ability of gypsum, a common sulfate mineral, to host arsenic atoms in its crystalline structure, is 1 demonstrated through experimental structural studies of the solid solutions formed upon synthetic co-2 precipitation of gypsum (CaSO 4 ·2H 2 O) and arsenic. Neutron and X-ray diffraction methods show an 3 enlargement of the gypsum unit cell proportional to the concentration of arsenic in the solids and to the 4 pH solution value. The substitution of sulfate ions (SO 4 2-) by arsenate ions is shown to be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Gypsum (CaSO 4 ·2H 2 O) is generated during Fe(III)-As(V) coprecipitation process because of the use of lime as base for neutralization [15]. Arsenic can be incorporated into gypsum lattice structure via isomorphic substitution for sulfate as unambiguously evidenced by neutron diffraction [16,17]. This finding is confirmed by a latest study using singlecrystal electron paramagnetic resonance spectroscopy (EPR) and pulsed electron nuclear double resonance spectroscopy (ENDOR) [18].…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Gypsum (CaSO 4 ·2H 2 O) is generated during Fe(III)-As(V) coprecipitation process because of the use of lime as base for neutralization [15]. Arsenic can be incorporated into gypsum lattice structure via isomorphic substitution for sulfate as unambiguously evidenced by neutron diffraction [16,17]. This finding is confirmed by a latest study using singlecrystal electron paramagnetic resonance spectroscopy (EPR) and pulsed electron nuclear double resonance spectroscopy (ENDOR) [18].…”
Section: Introductionmentioning
confidence: 74%
“…This is similar to the incorporation of arsenate ions into jarosite structure by substitution of sulfate [19] and vice versa incorporation of sulfate ions into scorodite structure by substitution of arsenate [20,21]. Fernández-Martínez et al [16,17] estimated the concentration of arsenic incorporated into the bulk of gypsum by interpolating the experimental and theoretical volume expansion data. The results indicated that more arsenic could be incorporated into gypsum at higher pH.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The main mechanisms of these include the adsorption of arsenate via surface complex on iron oxides (hematite goethite) and ferrihydrite mainly as an inner-sphere bidentate complex [16][17][18][19] and the formation of insoluble Fe-As compounds, ferric arsenate, scorodite and poorly crystalline ferric arsenate [20][21][22]. Additionally, Al ions, hydroxide and oxide of aluminum also showed good behaviors in adsorbing arsenic as well as Fe [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that the mobility and bioavailability of As are usually closely related to its host phases (i.e., minerals in many cases; Foster et al, 1998;Courtin-Nomade et al, 2009;Walker et al, 2009). Therefore, significant efforts have been devoted to the identification and development of minerals (or their synthetic equivalents) that are capable of fixing or minimizing the mobility and bioavailability of As in the environment (e.g., Bothe and Brown, 1999;Di Benedetto et al, 2006;Blanchard et al, 2007;Fernández-Martínez et al, 2008;Lee et al, 2009;Drahota and Filipi, 2009).…”
Section: Introductionmentioning
confidence: 99%